Fine Water: A Blind Taste Test. (26th April 2018) - Capehart, Kevin W.; Berg, Elena C.
Abstract: To test whether consumers can distinguish among different bottled waters and, if so, whether they prefer some to others, we recruited more than 100 subjects to participate in a blind taste test that consisted of four brands of bottled water featured in a restaurant's water menu and a guidebook to fine waters. The tasting involved three successive experiments. First, our subjects tried to distinguish bottled waters in a sensory discrimination test. They were only slightly better than random chance at doing so. Next, they rated bottled waters and tap water on a 14-point scale used at an international water competition. Some subjects preferred the inexpensive tap water to any of the bottled waters, and there was no association or a weak negative association between a bottled water's price and its rating. Finally, our subjects tried to distinguish tap from bottled water while matching the bottled waters to expert descriptions. They were no better than random chance at doing either of those things. Similar results have been found in previous taste tests of beer and wine. Overall, our results suggest consumers do not have strong preferences over different bottled waters to the extent they can even tell a difference. (JEL Classifications: D12, Q25)